2019
DOI: 10.3390/su11185103
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Factors Affecting Car Sharing Use Intention in the Southeast-Asia Region: A Case Study in Java, Indonesia

Abstract: This paper provides some insight into factors influencing the car sharing adoption and usage in Southeast-Asian developing countries like Indonesia, where car sharing is just emerging and so far, not effectively existent. This study uses an internet survey of 600 Indonesian respondents to examine how underlying factors, such as perceived benefits of car sharing related to convenience and cost-saving aspects, perceived risks and burdens of car ownership, and perceived values of car ownership as societal status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 52 publications
2
14
0
1
Order By: Relevance
“…Cartenì et al , 2016; Coll et al , 2014; Kang et al , 2016). Other factors include convenience (Orski, 2001; Peterson and Simkins, 2019), mobility patterns, family decisions, cost, and quality of alternative transport modes, lifestyle, and customer segment (Chun et al , 2019; Hahn et al , 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cartenì et al , 2016; Coll et al , 2014; Kang et al , 2016). Other factors include convenience (Orski, 2001; Peterson and Simkins, 2019), mobility patterns, family decisions, cost, and quality of alternative transport modes, lifestyle, and customer segment (Chun et al , 2019; Hahn et al , 2020).…”
Section: Resultsmentioning
confidence: 99%
“…However, Hjorteset and Böcker (2020) did not distinguish between P2P and B2C customers, and results may vary by carsharing type. While carsharing in the developed economies of Europe and North America is used predominantly by highly educated individuals (Boldrini et al , 2019; Clewlow, 2016; Coll et al , 2014; Hjorteset and Böcker, 2020; Münzel et al , 2020), Chun et al (2019) reported that the opposite is true for developing economies, where highly educated individuals are more likely to favor car ownership.…”
Section: Resultsmentioning
confidence: 99%
“…The intention to use carsharing services and the impact on the intent of the intended benefits of sharing a car, perceived risks and burden of ownership, perceived values of car ownership, such as social status [64].…”
Section: Preferences Intention Motivationmentioning
confidence: 99%
“…Sharing can improve car usage and reduce parking cost [ 2 , 3 ]. Moreover, most car-sharing systems provide services with electric car fleet [ 4 – 9 ]. Therefore, such system can alleviate urban problems such as excessive vehicle ownership [ 10 – 12 ], limited parking space [ 13 ], and environmental degradation [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite these advantages, the new business faces severe challenges [ 9 , 14 , 23 ]. Car-sharing platform with more rental sites and larger car fleet can offer more user flexibility; however, this would require greater investment.…”
Section: Introductionmentioning
confidence: 99%